Property Inheritance, Deferred Reference and Copredication. (23rd December 2021) - Gotham, Matthew
Abstract: There are sentences that are coherent and possibly true, but in which there is at the very least the appearance of a conflict between the requirements of two (or more) predicates that are applied to the same argument. This phenomenon, known as copredication, raises various issues for linguistic theory. In this paper I defend and develop an approach to the issues of counting and individuation in copredication put forward in previous work, in dialogue with criticisms made by Liebesman & Magidor and their own positive account of copredication.